2016
DOI: 10.1080/09168451.2016.1204220
|View full text |Cite
|
Sign up to set email alerts
|

Using severity factor as a parameter to optimize krill treatment under subcritical water conditions

Abstract: The aim of this study was to optimize the conditions for subcritical water treatment of krill, as expressed with a single parameter: the severity factor (log R). Raw krill was treated under subcritical water conditions at various log R values (1.54-3.75) by varying the treatment temperatures (120-180 °C) and times (0-10 min) in two different sizes of batch-type vessel (10 and 117 mL). The log R value could efficiently describe changes in various properties of the obtained liquid extracts and solid residues. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In addition, HPLC analysis showed unidentified peaks, as well as glucose, but the fraction of unidentified peaks was small (<1%), even with long heating times. It is possible that glucose might be further converted to other isomers, including mannose and fructose, in arginine solution (Kobayashi et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HPLC analysis showed unidentified peaks, as well as glucose, but the fraction of unidentified peaks was small (<1%), even with long heating times. It is possible that glucose might be further converted to other isomers, including mannose and fructose, in arginine solution (Kobayashi et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, as part of our search for simple and green methods for producing rare sugars, our group has studied the feasibility of using arginine as a catalyst for producing rare ketose and aldose isomers from common monosaccharides at high temperatures (Khuwijitjaru & Adachi, 2023a, 2023b; Khuwijitjaru et al, 2023; Kobayashi et al, 2023; Milasing et al, 2023). Arginine is a basic amino acid that is widely used as a food additive.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these characteristics, subcritical water has attracted a signifi-cant amount of attention as a reaction solvent and extractant. We have previously reported that the treatment of Isada krill [8][9][10][11][12] or its residual waste solution [13] under subcritical water conditions at 140 to 200℃ reduced the fishy odor and enhanced shrimp-like flavor.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the treatment of Isada krill [6][7][8][9][10], or that of its residual waste solution [11], under subcritical water conditions at 140-200℃ reduced the fishy odor and enhanced shrimp-like flavor.…”
Section: Introductionmentioning
confidence: 99%